Female participation increases and gender segregation - Claire Keane; Helen Russell; Emer Smyth (The Economic and Social Research Institute (ESRI), 2017)
This article examines the impact of a large increase in female participation on occupational segregation. Increases in female participation may decrease occupational segregation if women enter male dominated sectors but may increase segregation if they enter already female dominated sectors. Using Ireland as a test case due to the recent large increase in female participation rates, we firstly carry out a decomposition analysis between 1991 and 2006 and find that the rise in female employment was driven predominantly by increased demand while between one tenth and one fifth of the rise was due to women increasing their share of occupational employment. Formal measures of segregation show that occupational segregation fell over this time period. The formal measures of segregation show that the level of occupational grouping is important with stagnation or smaller falls in segregation using a broad occupational grouping and sharper falls using a more detailed occupational grouping. Our findings support previous U.S. research that found a rise in female participation resulted in a decline in occupational segregation.
Keywords: 330; gender; labour market; occupational segregation